In vitro Interaction of Pseudomonas aeruginosa Biofilms With Human Peripheral Blood Mononuclear Cells - Kaya, Esingül; Grassi, Lucia; Benedetti, Arianna; Maisetta, Giuseppantonio; Pileggi, Carolina; Di Luca, Mariagrazia; Batoni, Giovanna; Esin, Semih (Frontiers in Cellular and Infection Microbiology, 2020)
The human immune cell response against bacterial biofilms is a crucial, but still poorly investigated area of research. Herein, we aim to establish an in vitro host cell-biofilm interaction model suitable to investigate the peripheral blood mononuclear cell (PBMC) response to Pseudomonas aeruginosa biofilms. P. aeruginosa biofilms were obtained by incubating bacteria in complete RPMI 1640 medium with 10% human plasma for 24 h. PBMC obtained from healthy donors were added to preformed P. aeruginosa biofilms. Following a further 24 h incubation, we assessed i) PBMC viability and activation; ii) cytokine profiles in the supernatants; and iii) CFU counts of biofilm forming bacteria. Cell-death was less than 10% upon 24 h incubation of PBMC with P. aeruginosa biofilms. PBMC incubated for 24 h with preformed P. aeruginosa biofilms were significantly more activated compared to PBMC incubated alone. Interestingly, a marked activation of CD56+CD3 natural killer (NK) cells was observed that reached 60% of NK cells as an average of different donors. In the culture supernatants of PBMC co-cultured with P. aeruginosa biofilms, not only pro-inflammatory (IL-1, IFN-, IL-6, and TNF-α) but also anti-inflammatory (IL-10) cytokines were significantly increased as compared to PBMC incubated alone. Furthermore, incubation of biofilms with PBMC, caused a statistically significant increase in the CFU number of P. aeruginosa, as compared to biofilms incubated without PBMC. In order to assess whether PBMC products could stimulate the growth of P. aeruginosa biofilms, we incubated preformed P. aeruginosa biofilms with or without supernatants obtained from the co-cultures of PBMC with biofilms. In the presence of the supernatants, the CFU count of biofilm- derived P. aeruginosa, was two to seven times higher than those of biofilms incubated without supernatants (P<0.01). Overall, the results obtained shed light on the reciprocal interaction between human PBMC and P. aeruginosa biofilms. P. aeruginosa biofilms induced PBMC activation and cytokine secretion but, in turn, the presence of PBMC and/or PBMC-derived components enhanced the number of P. aeruginosa biofilm associated bacteria. This may indicate a successful bacterial defensive/persistence strategy against immune response.